Intelligent Fault Diagnosis and Remaining Useful Life Prediction of Rotating Machinery - Lei, Yaguo (Elsevier Science & Technology, 2016)
Intelligent Fault Diagnosis and Remaining Useful Life Prediction of Rotating Machinery provides a comprehensive introduction of intelligent fault diagnosis and RUL prediction based on the current achievements of the author's research group.